2008
DOI: 10.1021/jp802002k
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Complexity in the Electrochemical Oxidation of Thiourea

Abstract: We explored the temperature-dependent dynamics of the electrochemical oxidation of thiourea under potentialcontrol mode and found complex oscillations with one large peak and one small peak per period. Adjusting the temperature caused the relative amplitudes and positions of the two peaks to vary. Experiments showed that there were two distinct oscillatory regimes as a function of the external current, and at some temperatures, three-frequency quasiperiodic oscillations occurred for current densities between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…With the excess amount of hydrogen peroxide, the final oxidation product, sulfate, was identified by adding BaCl 2 solution to the acidified reaction solution. Figure 5 Through HPLC-MS analysis of species in the oxidation of FDS by hydrogen peroxide, urea (NH 2 ) 2 CO was detected ([M + H] + = 61.2), consistent with the previous study [19]. The influence of [H 2 O 2 ] 0 /[FDS] 0 on the reaction rate con- n , the expression of k can be converted to k = k h + k 1 in which k 1 is the pseudo-first order apparent rate-constant for FDS oxidation.…”
Section: Oxidation Kinetics Of Fdssupporting
confidence: 90%
See 1 more Smart Citation
“…With the excess amount of hydrogen peroxide, the final oxidation product, sulfate, was identified by adding BaCl 2 solution to the acidified reaction solution. Figure 5 Through HPLC-MS analysis of species in the oxidation of FDS by hydrogen peroxide, urea (NH 2 ) 2 CO was detected ([M + H] + = 61.2), consistent with the previous study [19]. The influence of [H 2 O 2 ] 0 /[FDS] 0 on the reaction rate con- n , the expression of k can be converted to k = k h + k 1 in which k 1 is the pseudo-first order apparent rate-constant for FDS oxidation.…”
Section: Oxidation Kinetics Of Fdssupporting
confidence: 90%
“…Investigations during the past couple of decades indicated that the oxidation processes displayed extremely rich nonlinear phenomena including autocatalysis, autoinhibition, bistability, oligooscillations, oscillations, birhythmicity, chaos, and spatiotemporal pattern [110]. When TU was oxidized on a platinum electrode, period-doubling bifurcation, two-and threefrequency quasi-periodic and other complex oscillatory phenomena can be observed [18,19]. To uncover the core oscillatory mechanism underlying such phenomena, extensive efforts [5,6,10,20] were devoted to the study of these reactions, indicating that formamidine disulfide (FDS, H 2 N(=NH)CS-SC(=NH)NH 2 ) is an important intermediate in the oxidation of TU.…”
Section: Introductionmentioning
confidence: 99%
“…25 In the oscillatory electrochemical urea system two-frequency quasiperiodic oscillation is transformed to three-frequency oscillations with increase in temperature. 35 Our experiments show that the phase coherent chaotic dissolution at low temperature becomes non-phasecoherent at elevated temperatures. The synchronization properties of phase coherent chaotic oscillations are quite different from those of non-phase-coherent oscillators; 12,16 therefore, nickel dissolution could be used as an experimental test bed for studying different, phase diffusion dependent routes to synchrony.…”
Section: Discussionmentioning
confidence: 64%
“…This was achieved with a core driven software PAR 283 Potentiostat/Galvanostat (PG/GS) and a Z-plot driven solartron instrument [3]. Cleaning of the electrodes was done prior to the experiment, for the purpose of revealing the surface of the electrodes which might have been covered by impurities, and conditioned them for the experiment as reported by Feng et al, [10]. The 0.5 M HCl was prepared, and the electrodes were immersed in the diluted solution.…”
Section: Materials and Instrumentationsmentioning
confidence: 99%